Safety, tolerability, pharmacokinetics, and subjective effects of 50, 75, and 100 µg LSD in healthy participants within a novel intervention paradigm: A proof-of-concept study. (March 2022) - Family, Neiloufar; Hendricks, Peter S; Williams, Luke TJ; Luke, David; Krediet, Erwin; Maillet, Emeline L; Raz, Shlomi
Background: Classic psychedelics hold promise as therapeutics for psychiatric disorders, but require scalable intervention protocols. This proof-of-concept study evaluated the safety, tolerability, pharmacokinetics, and subjective effects of 50, 75, and 100 µg lysergic acid diethylamide (LSD) in healthy adults within a novel intervention paradigm. Methods: Up to three participants were administered LSD on the same day in separate rooms, each with a single attendant, after 1 day of preparation. An open-label design and a double-blind placebo-controlled design were used. Results: Ninety-one percent of participants completed the study. Thirty-two adults (mean age = 28.8 years) received 50 (n = 3), 75 (n = 7), 100 (n = 3) LSD, 50 µg followed by 75 µg LSD (n = 9) 1 week apart, or placebo followed by a 75 µg LSD (n = 10) 1 week apart. There were no serious adverse events. Twenty-eight percent of participants experienced at least one expected mild adverse event, with one expected moderate adverse event. The maximum blood plasma levels occurred between 1.2 and 2 h post-administration, with an apparent half-life between 2.8 and 4.3 h. LSD largely induced greater subjective effects versus placebo. Conclusion: In the current novel intervention paradigm, 50, 75, and 100 µg LSD are tolerable with favourable safety profiles in healthy adults, only mild adverse events during the day of drug administration, and mystical-type subjective experiences. Future studies are needed to evaluate safety, tolerability, subjective effects, and cost-effectiveness in clinical populations.